Computational simulations of hybrid mediated nano- hemodynamics (Ag-Au/Blood) through an irregular symmetric stenosis. (March 2021) - Tripathi, Jayati; Vasu, B.; Bég, O. Anwar
Abstract: This article examines theoretically and numerically the unsteady two-dimensional blood flow through a diseased artery featuring an irregular stenosis. An appropriate geometric model is adopted to simulate the irregular stenotic artery. Inspired by drug delivery applications for blood vessels, the impact of hybrid nanoparticles on blood flow using a modified Tiwari-Das model is discussed. The blood is examined to have a homogenous suspension of hybrid nanoparticles. Reynolds' viscosity model is applied in the formulation to represent the temperature dependency of blood. The two-dimensional governing conservation equations for momentum and heat transfer with buoyancy effect are simplified by considering the mild stenotic approximation. A finite-difference technique is deployed to numerically discretize the transformed non-dimensional model. Extensive graphical results for blood flow characteristics are obtained by MATLAB code. Comprehensive visualization of the effects of hemodynamic, geometric and nanoscale parameters on transport characteristics is provided. The problem is conducted for silver and silver-gold hybrid mediated blood flow models, and experimental values of blood and these biocompatible metallic nanoparticles. A comparison between silver and hybrid nanofluid is obtained which promotes the use of hybrid nanoparticles in successfully achieving clinically more beneficial results associated with nano-drug delivery in diseased hemodynamics. Enhancement in viscosity parameter induces axial flow acceleration in the stenotic region while lower thermal conductivity decreases the temperature magnitudes. Furthermore, with time variation, the pressure gradient is found to be lower in coronary arteries comparatively to femoral arteries. The simulations are relevant to transport phenomenon in nano-drug targeted delivery in haematology. Highlights: This research examines theoretically and numerically the unsteady blood flow through a diseased artery with irregular stenosis. Inspired by drug delivery applications, Extensive visualization of the effects of hemodynamic, geometric and nanoscale parameters are provided. Reynolds' model is deployed to represent the temperature dependency of blood viscosity. Wall shear stress and flow rate values are enhanced for hybrid nanofluids compared to unitary nanofluid. Enhancement in viscosity parameter induces axial flow acceleration in the stenotic region while lower thermal conductivity decreases temperatures.